A Brief Note on Coherent Feedback in Semiconductor Lasers. (1994) - Caffaro, M. A. Grado; Caffaro, M. Grado
Abstract : Some aspects on coherent feedback in a laser diode are investigated. In particular, weak optical feedback is considered in the context of the feedback-induced frequency shift. In addition, the Lang-Kobayashi equations are considered.